Are you kidding?
1.04 ( cos A )² + 0.2 ( cos A ) - 0.75 = 0
Divide both sides by 1.04
1.04 ( cos A )² / 1.04 + 0.2 ( cos A ) / 1.04 - 0.75 / 1.04 = 0 / 1.04
( 1.04 / 1.04 ) ∙ ( cos A )² + ( 0.2 / 1.04 ) ∙ ( cos A ) - 0.75 / 1.04 = 0
1 ∙ ( cos A )² + ( 0.2 / 1.04 ) ∙ ( cos A ) - 0.75 / 1.04 = 0
( cos A )² + 0.19231 ( cos A ) - 0.72115 = 0
approx.
( cos A )² + 0.192 ( cos A ) - 0.721 = 0
does anybody know how 1.04(cosA)^2 + 0.2(cosA) -0.75 = 0 become (cosA)^2 + 0.192(cosA) - 0.721 = 0
2 answers
Magic math.